THE MILITARY ESCALATION BY THE ARCTIC FIVE MEMBERS IN THE ARCTIC OVER THE PERIOD OF 2007 - 2019 - Benita Sashia Jayanti; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The Arctic recently has shifted into one of the most appealing topic to be debated in terms of International Politics. The Arctic Five, membered by the United States, Denmark, Canada, Norway, and Russia are undergoing military escalation in the Arctic. Some precedings reports have linked the correlation between the military escalation with the dispute of territorial claims and the abundant of natural resources lying under the bottom of the Arctic Ocean. Perceiving that early conclusion given to this case, writer is being skeptical. The main object of this research is to discover the driven factors causing the military escalation in the Arctic. Throughout the research, writer analyses the case using the defensive realism theory with qualitative method and descriptive research by using literature review. At the end of the research, result is pointing out that the territorial dispute and natural resource are not the main driving factors causing the military escalation. The military escalation is not being used to threat other countries and it is only part of the capabilities fulfillment which has to be done by every country to attain the maximum security and survive within the anarchical international system.